Globalization and formal sector migration in Brazil - Ernesto Aguayo-Tellez; Marc-Andreas Muendler; Jennifer Pamela Poole (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2008)
We use novel linked employer–employee data to study the relationship between globalization and formal sector interstate migration for Brazil. We estimate the worker's multichoice migration problem and document that previously unobserved employer covariates are significant predictors associated with migration flows. Our results provide support for the idea that globalization acts on internal migration through the growth of employment opportunities at locations with a high concentration of foreign owned establishments and the stability of employment at exporting establishments. A 1 per cent increase in the concentration of foreign owned establishments at potential migration destinations is associated with a 0.2 percentage point increase in the migration rate, and a 1 per cent increase in exporter employment predicts a 0.2 percentage point reduced probability of migration. – migration ; globalization ; policy reforms ; Brazil
Keywords: R23; O15; J61; 330; Binnenwanderung; Globalisierung; Brasilien